Blood transfusion of the donor is associated with stage 3 primary graft dysfunction after lung transplantation. Issue 9 (4th July 2021) - Elmaleh, Yoann; De Tymowski, Christian; Zappella, Nathalie; Jean‐Baptiste, Sylvain; Tran‐Dinh, Alexy; Tanaka, Sébastien; Yung, Sonia; Lortat‐Jacob, Brice; Mal, Hervé; Castier, Yves; Atchade, Enora; Montravers, Philippe
Abstract: Background: The first aim of this study was to assess the association between stage 3 PGD and pre‐donation blood transfusion of the donor. The secondary objectives were to assess the epidemiology of donor transfusion and the outcome of LT recipients according to donor transfusion status and massive donor transfusion status. Methods: This was an observational, prospective, single‐center study. The results are expressed as absolute numbers, percentages, medians, and interquartile ranges. Statistical analyses were performed using Chi squared, Fischer's exact tests, and Mann‐Whitney U tests ( P  < .05 was considered significant). A multivariate analysis was performed. Results: Between January 2016 and February 2019, 147 patients were included in the analysis. PGD was observed in 79 (54%) patients, 45 (31%) of whom had stage 3 PGD. Pre‐donation blood transfusion was administered in 48 (33%) donors (median of 3[1–9] packed red cells (PRCs)). On multivariate analysis, stage 3 PGD was significantly associated with donor blood transfusion (OR 2.69, IC (1.14–6.38), P  = .024). Mortality at days 28 and 90 was not significantly different according to the pre‐donation transfusion status of the donor. Conclusion: Pre‐donation blood transfusion is associated with stage 3 PGD occurrence after LT. Transfusion data of the donor should be included in donor lung assessment.